How Do the Osteoporotic Changes Affect the Maxillary Bone Structure in Women Over 40 Years? - Yücesoy, Türker; Şeker, Elif Dilara; Özsoy, Zeynep (Cerrahpaşa Medical Journal, 2022)
Objective: This study aimed to evaluate how osteoporosis affects the morphological and structural features of the maxillary bone in osteopenic and osteoporotic patients. Methods: This study included 72 women over 40 years and were divided into 3 groups as osteoporosis group, osteopenia group, and normal group. In the midsagittal sections of conical beam computerized tomographies, several lengths and angles were measured, whereas Hounsfield unit values were measured in 5 regions of the maxilla in the axial sections. Results: The outcomes of the 3 groups were analyzed, and no significant difference was found except for the RPL angle that revealed statistically wider scores for the normal group than for the osteoporosis and osteopenia groups (P = .01 and P = .03, respectively). Moreover, the Hounsfield unit values were also analyzed, and no significant difference was detected between groups except for the outcomes of the left maxillary region. The Hounsfield unit value of this area was statistically lower in osteoporosis patients than in the normal group (P = .03). Conclusion: Left maxillary regions in the patients scored statistically lower Hounsfield unit values with which it could be concluded that these regions would reveal lower bone density in osteoporotic patients. Further studies must be carried out with more samples for early diagnosis of bony changes or additional parameters such as chewing side preferences and status of partial or total edentulous dentition should be evaluated. Cite this article as: Yücesoy T, Dilara Şeker E, Özsoy Z. How do the osteoporotic changes affect the maxillary bone structure in women over 40 years? Cerrahpaşa Med J. October 4, 2022. 2022;46(3):194-200.